The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/pr049967i
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for Analysis of the Phosphotyrosine Proteome and Its Application to the Chicken B Cell Line, DT40

Abstract: In this study, we have begun to analyze phosphotyrosyl and associated proteins present in a DT40 chicken B cell line overexpressing the nonreceptor protein-tyrosine kinase, Syk. An anti-phosphotyrosine antibody was used to select tyrosine-phosphorylated proteins. After tryptic digestion, peptides were subjected to a beta-elimination reaction and phosphotyrosine-containing peptides were enriched via immobilized metal affinity chromatography. Several known substrates and candidate substrates for Syk and the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In conclusion, we demonstrate that Syk positively affects the function of adherens junctions. Zolodz et al (2004) carried out a phosphoproteomic analysis on a Syk-negative chicken B cell line in which Syk expression was restored by transfection with murine Syk and activated with PV. Not using the quantitative SILAC approach, a significantly lesser amount of potential Syk signaling effector proteins were identified, excluding proteins expressed uniquely in nonhematopoietic cells such as the cell-cell adhesion and cell polarization components described above.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we demonstrate that Syk positively affects the function of adherens junctions. Zolodz et al (2004) carried out a phosphoproteomic analysis on a Syk-negative chicken B cell line in which Syk expression was restored by transfection with murine Syk and activated with PV. Not using the quantitative SILAC approach, a significantly lesser amount of potential Syk signaling effector proteins were identified, excluding proteins expressed uniquely in nonhematopoietic cells such as the cell-cell adhesion and cell polarization components described above.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, phophotyrosine is not sensitive to the belimination reaction. Zolodz et al [38] used this aspect as a tool for reduction in the complexity of a mixture of phosphopeptides prior to IMAC when searching for pTyrcontaining peptides.…”
Section: Chemical Modificationsmentioning
confidence: 99%
“…pTyr‐containing proteins can be first purified from whole cell lysate by IP using anti‐pTyr monoclonal antibodies. After tryptic digestion, phosphopeptides were further enriched by IMAC and analysed by LC‐MS (Zolodz et al, 2004; Zheng, Hu, Quinn, & Wang, 2005). Lombardi combined IP (with a mixture of pY100, 4G10, and PT66) and TiO 2 enrichment, and demonstrated that this IP‐TiO 2 strategy was more comprehensive for enriching phosphopeptides and allowed the identification of a large set of proteins known to be phosphorylated (715 protein groups) (Lombardi et al, 2015).…”
Section: Enrichment Strategies For Phosphoproteome Analysismentioning
confidence: 99%